The Importance Of Economy For An Ideal Life - Abdullah AF; Achmad Abubakar; Hasyim Haddade (CV Putra Publisher, 2023)
Allah created the earth as an expanse, that is, an expanse that is neither too hard nor too soft so that it is impossible for it to be permanently inhabited, also the sky as a shade, as a roof, and He sent down rainwater from the sky and then released it from it so that fruit would grow as sustenance for you. you eat and feed your cattle, do not make partners with Allah, for it is Allah who created all that is on earth. So, from economic development in everyday life, this has been deciphered in the Koran for humans, there are angels who always follow them in turn, in front of them and behind them, they guard them at the behest of Allah. Indeed, Allah does not change the condition of a people until they change what is in themselves. and if Allah wills bad for a people, then no one can refuse it; and there is no protector for them besides Him. 1) Train a Person to Develop Their Creativity in Entrepreneurship and Be Independent 30 Know the Management of Human Life 4) Organize and Manage the Economy within the Family Sphere 5) As an Agent of Change in Community Life